A conceptual and empirical study on the development of the Islamic donation-based crowdfunding platform model for micro small and medium-sized enterprises (MSMEs) in times of Covid-19 pandemic in Indonesia - Sulaeman Sulaeman (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: This study aims to present and to test practically the concept of the Islamic donation-based crowdfunding platform model for providing the financing program of MSMEs in times of COVID-19 pandemic in Indonesia.Methodology: This study uses a conceptual and empirical approach. The primary data is collected through the online survey questionnaires and then the data are descriptively analyzed.Findings: This research finds that the concept of the Islamic donation-based crowdfunding platform model is expected to solve the existing problems due to the adverse impact of the Covid-19 pandemic on MSMEs in Indonesia. Also, the platform model will open the opportunity for more optimum and impactful utilization of Islamic charity donation funds from zakat, cash waqf, sadaqah, and the like. Besides, an empirical study finds the majority of respondents accepted the concept of the Islamic donation-based crowdfunding platform model. The platform model has the potential to optimize financing programs for MSMEs in times of the Covid -19 pandemic situation.Practical implications: The present study also has implications for government, zakat institution, waqf institution, and policymakers to realize the concept of the Islamic donation-based crowdfunding platform model into the real world.Originality: The study will contribute to the existing literature especially on the Islamic donation-based crowdfunding platform model as an alternative strategy to minimize the negative impact of the Covid-19 pandemic on MSMEs in Indonesia.